Smart Innovations and Sustainability in EU Waste Material Trading: Evidence of Quantile Decomposition in EU Circular Economy Transitions - Eszter Lukács; Peter Németh; Md. Rashed; Mohammad Fakhrul Islam (Circular Economy and Sustainability, 2026)
Europe stands at the threshold of a transformative circular economy transition across the European Union (EU). However, to achieve a sustainable framework that improves resource use, transforms waste generator behavior, and guides high-polluting industries toward circular practices, the EU needs more efficient recovery networks and material circulation across member states. Using 14 years of cross-border waste recovery data from 2010 to 2023 across 27 EU countries, this study investigates the heterogeneous associations of several determinants of exports of notified waste for recovery (EWR) through the method of moments quantile regression (MMQR) to decompose location (median) and scale (dispersion) effects, alongside bootstrap quantile regression (BSQR) for robustness, the generalized method of moments (GMM) for persistence and endogeneity, and Granger causality tests for directional relationships. Our investigation identifies several policy factors associated with transboundary recovery participation and circular economy transition. The relationship also shows reverse Granger causality. AI innovation shows no significant associations with waste trade or the possibility of deployment gaps, but R&D intensity shows robust positive associations across all quantiles, with forward Granger causality supporting causal precedence. The recycling rate of municipal waste (RMW) has monotonically increasing associations in all quantiles and has bidirectional Granger causality, implying possible feedback mechanisms. These findings, put together, inform policymakers to consider market mechanisms, institutionalizing R&D investment, emphasizing infrastructure development, driving economic growth, and leveraging technological capabilities to support sustainable transboundary waste recovery networks and circular transition across the EU.

Otolith weight as a predictor of age in Sillaginopsis panijus (Hamilton, 1822): Development of a preliminary age estimation model - Mohammad Rashed; KM Jakaria Shuvo; Siam Sheikh Sadi; Md Abdul Baten (Estuarine, Coastal and Shelf Science, 2026)

The feasibility of calculating the enrichment of 235U using the PIGE method with high-energy protons - Marzieh Hassanpour; Mehdi Hassanpour; MohammadReza Rezaie; Mohammad Rashed Iqbal Faruque (Annals of Nuclear Energy, 2026)

Combined Effects of Parasitic Infection and Heavy Metal Exposure on Health and Profitability of Cultured African Catfish (Clarias gariepinus) - Mahmoud Radwan; Mohammad R. K. Abdel-Samad; Aya Ramadan Rashed; Wafa Mohammed Al-Otaibi; Shahd Yassir; Moussa Attia Moussa (Biological Trace Element Research, 2025)

Nutrient Analysis of Raw and Sensory Evaluation of Cooked Red Tilapia Fillets (Oreochromis sp.): A Comparison Between Aquaculture (Red Kenyir™) and Wild Conditions - Aswir Abd Rashed; Nurliayana Ibrahim; Nurul Izzah Ahmad; Mariam Marip; Mohd Fairulnizal Md Noh; Mohammad Adi Mohammad Fadzil (Fishes, 2025)
The tilapia sector is advancing due to breakthroughs in aquaculture techniques and genetic enhancements. Comprehending sensory qualities is crucial for producers striving to meet market demands efficiently. As consumer preferences play a significant role in shaping the market, enhancing the sensory attributes of both farmed and wild red tilapia will be key to ensuring their success in the competitive aquaculture industry. One of Malaysia’s most prominent aquaculture projects is the Como River Aquaculture Project located in Kenyir Lake, where tilapia fish farming, trademarked as Red Kenyir™, is conducted. Thus, this study aimed to evaluate the nutrient analysis of raw and five sensory attributes (appearance, texture, smell, taste, overall quality) of filets from Red Kenyir™ and wild red tilapia (Oreochromis sp.). Red Kenyir™ were fed three different commercial diets (A, B, and C) from fingerling to adulthood, while wild tilapia (W) was sourced from the market. Proximate and nutritional analyses were conducted based on the standard food analysis protocol by AOAC/AOCS. To the best of our knowledge, this is the first study to comprehensively document the nutrient analysis of raw and consumer sensory perception of cooked Red Kenyir™ aquaculture tilapia in direct comparison with wild red tilapia. The sensory evaluation was conducted using a consumer preference test. Statistical analysis was performed using SPSS. Nutrient analysis showed that Red Kenyir™ tilapia had lower fat (0.25–1.37 g/100 g vs. 4.30 g/100 g) and lower energy (77.38–113.46 kcal/100 g vs. 132.79 kcal/100 g) levels. Protein levels varied across groups (19–26.54 g/100 g vs. 22.95 g/100 g). The tryptophan content of the Red Kenyir™ tilapia samples ranged between 0.13 and 0.23 g/100 g, while the wild tilapia contained 0.19 mg/100 g. Sensory evaluation with 36 panelists revealed no significant differences in appearance, texture, or smell (p > 0.05). However, wild tilapia scored slightly higher in taste (4.14) than Red Kenyir™ (3.54–3.71) for steamed preparation (p

Environmental sustainability practices in SMEs: Insights from integrated PLS-SEM and fsQCA approaches - Mohammad Imtiaz Hossain; Yasmin Jamadar; Mohammad Fakhrul Islam; Md. Rashed; Tania Akter (Journal of Cleaner Production, 2025)

Genome-wide analysis of TCP family genes and their constitutive expression pattern analysis in the melon (Cucumis melo) - Md Jahid Hasan Jone; Md Nure Adil Siddique; Manosh Kumar Biswas; Mohammad Rashed Hossain (Genes & Genomics, 2025)

Capacity of detergent to increase the efficacy of bio-pesticides and chemical pesticides against giant mealybug, Drosicha mangiferae (Homoptera: Pseudococcidae) - Mohammad Shaef Ullah; Md. Mehedi Hassan Sharif; Ayon Dey; Md. Mojammel Haque; Md Tafsir Nur Nabi Rashed (International Journal of Tropical Insect Science, 2024)

Unraveling the impact of greenhouse pepper resistance on biological performance of the broad mite Polyphagotarsonemus latus (Acari: Tarsonemidae) - Elnaz Fadaei; Mohammad Mehrabadi; Abdoolnabi Bagheri; Arash Rashed; Yaghoub Fathipour (Crop Protection, 2024)

A continuous flow microreactor as a practical tool for the synthesis of active pharmaceutical ingredients - K. Vijaya Bhaskar; Mohammad Rashed; K. Subrahmanya Bhat; Jechan Lee; Ki-Hyun Kim; Kezia Buruga (Process Safety and Environmental Protection, 2024)

Sensitivity analysis of cumulus parameterization scheme and data sources to simulate thunderstorms over Bangladesh using WRF model - M. Mozammel Hoque; Md. Salah Uddin Afsar; Mohammad Rashed Iqbal Faruque; S. Jamal Ahmed; A.T.M. Kaosar Jamil; M.A.K. Mallik; S.M. Quamrul Hassan (Advances in Space Research, 2024)

Which soil properties could affect the floristic composition of weed communities in saffron fields - Obaidullah Ghafory; Ghorban Ali Asadi; Mehdi Rastgoo; Mohammad Hassan Rashed Mohassel; Abdollah Mollafilabi (Biologia, 2024)

Publisher Correction: Heat Stress Modulates Superoxide and Hydrogen Peroxide Dismutation and Starch Synthesis during Tuber Development in Potato - Jobadatun Naher; Zahid Hasan Sabuj; Sahida Islam Sumona; Sheba Pada Chakraborty; Mohammad Rashed Hossain; Md. Motiar Rohman; Ujjal Kumar Nath (American Journal of Potato Research, 2024)

Heat Stress Modulates Superoxide and Hydrogen Peroxide Dismutation and Starch Synthesis during Tuber Development in Potato - Jobadatun Naher; Zahid Hasan Sabuj; Sahida Islam Sumona; Sheba Pada Chakraborty; Mohammad Rashed Hossain; Md. Motiar Rohman; Ujjal Kumar Nath (American Journal of Potato Research, 2024)

Linking green supply chain management practices and environmental performance in the manufacturing industry: a hybrid SEM-ANN approach - Rashed Al Karim; Mohammad Rokibul Kabir; Md Karim Rabiul; Sakia Kawser; Abdus Salam (Environmental Science and Pollution Research, 2024)

Improved performance of land-fixed oscillating water column through dual chamber design - Heath Palmer; Ming Zhao; Helen Wu; Pan Hu; Mohammad Rashed Mia; Chengwang Lei (Ocean Engineering, 2023)

Characterization and distribution of black rot disease causing pathogen-Xanthomonas campestris pv. campestris races of the Jeju Island, South Korea - Jeong-Eui Hong; Hee-Jin Kim; Mohammad Rashed Hossain; Mehede Hassan Rubel; Nihar Sahu; Sopheap Mao; Jong-Goo Kang; Hoy-Taek Kim; Masao Watanabe; Jong-In Park (Journal of Plant Pathology, 2023)

An in vivo study: Prebiotic evaluation of the resistant Starch from Metroxylon sagu on obesity using fat-induced rats - Mayrilyn Solo Thompson; Tan Hui Yan; Kathleen Michelle Mikal; Shafarin Mohammad Shamsudin; Aswir Rashed; Shahrul Razid Sarbini (Bioactive Carbohydrates and Dietary Fibre, 2023)

The application of graphene/h-BN metamaterial in medical linear accelerators for reducing neutron leakage in the treatment room - Mehdi Hassanpour; Marzieh Hassanpour; Mohammadreza Rezaie; Saeedeh Khezripour; Mohammad Rashed Iqbal Faruque; Mayeen Uddin Khandaker (Physical and Engineering Sciences in Medicine, 2023)

High prevalence of multidrug-resistant Campylobacter jejuni in sheep and goats milk in Jordan - Mohammad M. Obaidat; Rashed M. Alshdaifat (International Dairy Journal, 2023)

Hydrodynamic Performance of a Floating Offshore Oscillating Water Column Wave Energy Converter - Mohammad Rashed Mia; Ming Zhao; Helen Wu; Vatsal Dhamelia; Pan Hu (Journal of Marine Science and Engineering, 2022)
A floating oscillating water column (OWC) wave energy converter (WEC) supported by mooring lines can be modelled as an elastically supported OWC. The main objective of this paper is to investigate the effects of the frequency ratio on the performance of floating OWC (oscillating water column) devices that oscillate either vertically or horizontally at two different mass ratios (m = 2 and 3) through two-dimensional computational fluid dynamics simulations. The frequency ratio is the ratio of the natural frequency of the system to the wave frequency. Simulations are conducted for nine frequency ratios in the range between 1 and 10. The hydrodynamic efficiency achieves its maximum at the smallest frequency ratio of 1 if the OWC oscillates horizontally and at the largest frequency ratio of 10 if the OWC oscillates vertically. The frequency ratio affects the hydraulic efficiency of the vertical oscillating OWC significantly stronger than that of the horizontal oscillating OWC, especially when it is small. The air pressure and the volume oscillation in OWC is not affected much by the horizontal motion of the OWC but is significantly affected by the vertical motion, especially at small frequency ratios.

Stock Assessment of Six Sciaenidae Species in the Bay of Bengal, Bangladesh Water Using a Length-Based Bayesian Biomass (LBB) Method - Rokeya Sultana; Qun Liu; Petra Schneider; Md. Abdullah Al-Mamun; Al Mamun; Md. Farhan Tazim; Mohammad Mojibul Hoque Mozumder; Mohammed Rashed Parvej; Md. Mostafa Shamsuzzaman (Fishes, 2022)
Six most abundant and commercially valuable croakers (Sciaenidae) stocks in the coastal water of Bangladesh were evaluated using a length-based Bayesian Biomass (LBB) approach. The ratios B/B0 (current relative biomass) were smaller than the BMSY/B0 in five of the six stocks. For the six estimated populations, two (Otolithes ruber and Pterotolithus maculatus) are grossly overfished, one (Otolithoides pama) is overfished, two (Johnius belangerii and Panna heterolepis) are slightly overfished, and only donkey croaker (Pennahia anea) is in the healthy (B/B0 > BMSY/B0) status. Furthermore, the optimal length at first capture (Lc_opt) was higher than the length at first capture (Lc) in four populations, indicating growth overfishing, suggesting that increasing mesh size would benefit the catch and biomass. Findings from the present study confirm the declining trend of fisheries resources, particularly the croaker species in the BoB, Bangladesh coastal water. Management strategies (such as effort control, choosing the appropriate mesh size, total allowable catch limit, identify and enhance protection of the feeding, breeding, and nursery ground, etc.) should be taken for the sustainable management and recovery of the country’s marine fishing resources, particularly the valuable croaker species.

Climate change vulnerability in Bangladesh based on trend analysis of some extreme temperature indices - Istiak Ahmed; Sheikh Ishtiaque; Taslima Zahan; Md. Saif Uddin Rashed; Ranjit Sen; Md. Faruque Hossain; Shyamal Brahma; Imrul Mosaddek Ahmed; M. Akhtar Hossain; Mohammad Akkas Ali; Abu Hena Sorwar Jahan; Sheikh Imtiaz; et al. (Theoretical and Applied Climatology, 2022)

Genetic diversity of Iranian wild barley (Hordeum spontaneum Koch.) populations - Mojtaba Hosseini; Mohsen Yassaie; Mohammad Hassan Rashed-Mohassel; Reza Ghorbani; Ali Niazi (Journal of Crop Science and Biotechnology, 2022)

How does tourist perception lead to tourist hesitation? Empirical evidence from Bangladesh - Mohammad Rashed Hasan Polas; Ratul Kumar Saha; Mosab I. Tabash (Environment, Development and Sustainability, 2022)

Spatial variability of climatic hazards in Bangladesh - Md. Arif Chowdhury; Rashed Uz Zzaman; Nusrat Jahan Tarin; Mohammad Jobayer Hossain (Natural Hazards, 2022)

The impact of Rumex vesicarius seed water extracts on mice fertility - Ahmad Rashed Alhimaidi; Aiman Abdullah. Ammari; Mohammad Khair Okla; Muath Qasem Algadi; Ramzi Ahmed Amran; Hissah Ibrahim Alhusayni; Mohammed Ahmad Alhimaidi (Environmental Science and Pollution Research, 2022)
Rumex vesicarius (RV) is an edible wild annual plant, and it is reported that it contains a good source of minerals, protein, and ascorbic acid. Several studies have indicated the anti-liver damage, anticancer, antimicrobial, and antioxidant properties of the RV plant. There are currently no reports regarding the effect of RV on fertility. Therefore, this study focuses on the impact of RV water seed extracts on mice fertility. RV plants were collected, and water seed extracts were prepared; 50 mg/kg body weight (BW) of this was then injected into the mice (male and female) using an oral feeding tube 5 days before mating (group I) or during caging of the females with the males for 1 week to detect their fertility rate. In the different female groups, no significant difference between their BW and their newborn’s BW in the treated and control groups was found. Female fertility, pregnancy, and offspring rates showed some variation within each female group and between the different female groups. In comparing the fertility and offspring rate between the different groups, there was a significant difference ( P < 0.05) between groups I and III females and between groups I and IV females, while the other groups showed no significant differences. In contrast, the other groups showed no significant differences. Regarding the impact of the water seed extract on males, the BW was approximately the same in control and treated males.

Seed germination and seedling emergence in two populations of eastern dodder (Cuscuta monogyna Vahl.): evaluation of environmental factors and burial depth - Esmail Ebrahimi; Ebrahim Izadi Darbandi; Mohammad Hassan Rashed Mohassel; Reza Tavakol Afshari (Acta Physiologiae Plantarum, 2022)

Plio-Pleistocene to Recent tectonostratigraphic evolution of the Lalmai anticline in the western Indo-Burman Range (Bangladesh): insights from lithofacies analysis and structural synthesis - Rashed Abdullah; Abu Sadat Md Sayem; Rumana Yeasmin; Mohammad Mashiur Rahman; Zahidul Bari; Farida Khanam (Arabian Journal of Geosciences, 2021)

In silico characterization and expression of disease-resistance-related genes within the collinear region of Brassica napus blackleg resistant locus LepR1′ in B. oleracea - Mostari Jahan Ferdous; Mohammad Rashed Hossain; Jong-In Park; Hoy-Taek Kim; Arif Hasan Khan Robin; Sathishkumar Natarajan; Manosh Kumar Biswas; Hee-Jeong Jung; Ill-Sup Nou (Journal of General Plant Pathology, 2020)

In-silico identification and differential expression of putative disease resistance-related genes within the collinear region of Brassica napus blackleg resistance locus LepR2’ in Brassica oleracea - Mohammad Rashed Hossain; Mostari Jahan Ferdous; Jong-In Park; Arif Hasan Khan Robin; Sathishkumar Natarajan; Hee-Jeong Jung; Hoy-Taek Kim; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)
Blackleg disease, caused by Leptosphaeria maculans, greatly affects the production of cabbage ( Brassica oleracea ). However, definitive R-gene(s) are yet to be identified in this crop. In contrast, a number of R-loci have been identified in A- or B-genome crops. Identification of few resistant cabbage genotypes indicates the presence of R-genes in this C-genome crop. High ancestral synteny between Brassica genomes suggests that the collinear regions of known A- or B-genome R-loci may also contain functional R-genes in the C-genome. Strong resistance was observed in the cotyledons of cabbage inbred line SCNU-98 against two L. maculans isolates, 03–02 s and 00–100 s. We investigated the collinear region of the Brassica napus blackleg resistance locus LepR2’ in B. oleracea since both isolates of L. maculans contain corresponding avirulence genes. The locus was collinear to a 5.8 Mbp genomic segment of B. oleracea chromosome C09 containing 13 genes that have putative disease resistance-related domains. High expression of genes Bo9g117290 and Bo9g111510 against isolate 00–100 s, and high expression of genes Bo9g126150 and Bo9g111490 against both isolates in the resistant-line SCNU-98 indicate their putative roles in blackleg resistance, which remained to be functionally verified. This work enhances our understanding of R-gene-mediated resistance to blackleg in cabbage.

Migration and Household Adaptation in Climate-Sensitive Hotspots in South Asia - Amina Maharjan; Ricardo Safra de Campos; Chandni Singh; Shouvik Das; Arjun Srinivas; Mohammad Rashed Alam Bhuiyan; Sultan Ishaq; Muhammad Awais Umar; Tanzina Dilshad; Krity Shrestha; Suruchi Bhadwal; Tuhin Ghosh; et al. (Current Climate Change Reports, 2020)
Purpose of Review South Asia is highly vulnerable to the impacts of climate change, owing to the high dependency on climate-sensitive livelihoods and recurrent extreme events. Consequently, an increasing number of households are adopting labour migration as a livelihood strategy to diversify incomes, spread risks, and meet aspirations. Under the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA) initiative, four research consortia have investigated migration patterns and their inherent linkages to adaptation to climate change in climate hotspots. This article synthesizes key findings in regional context of South Asia. Recent Findings The synthesis suggests that in climate-sensitive hotspots, migration is an important livelihood diversification strategy and a response to various risks, including climate change. Typically, one or more household members, often young men, migrated internally or internationally to work in predominantly informal sectors. Remittances helped spatially diversify household income, spread risks, and insure against external stressors. The outcomes of migration are often influenced by who moves, where to, and what capacities they possess. Summary Migration was found to help improve household adaptive capacity, albeit in a limited capacity. Migration was mainly used as a response to risk and uncertainty, but with potential to have positive adaptation co-benefits.

Modeling aquifer storage and recovery potential for seasonal water storage in the Flemish alluvial plains of Belgium using MODFLOW - Mohammad Rashed Wasif; Mohammad Mehedi Hasan (Arabian Journal of Geosciences, 2020)

Molecular characterization of Acidovorax citrulli strain NIHHS15-280 causing bacterial fruit blotch disease in Korea and screening of resistance sources in melon - Md. Rafiqul Islam; Mohammad Rashed Hossain; Hoy-Taek Kim; Ujjal Kumar Nath; Md. Abuyusuf; Hee-Jeong Jung; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)